2023
DOI: 10.3390/vaccines11071231
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Vaccine Hesitancy on the Relationship between the COVID-19 Vaccine Coverage Index and Vaccine Coverage

Abstract: To examine COVID-19 vaccination barriers in the US, this study drew on publicly available county-level data (n = 3130) to investigate the impact of vaccine hesitancy on the relationship between county-level social/structural barriers and vaccine coverage. A hierarchical regression was performed to establish the relationship between the COVID-19 Vaccine Coverage Index (CVAC) and vaccine coverage, assess the moderating effect of vaccine hesitancy on this relationship, and explore the influence of ethno-racial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Most of these variables specifically apply to the uncertain model, while all models acknowledge the significance of the level of concern. Previous research has reported an association between vaccine uptake in hesitant communities and their level of apprehension regarding the accessibility and distribution of vaccines [ 111 , 112 ]. To this end, regions facing greater hurdles in distributing vaccines, as gauged by the multidimensional CVAC index of concern, tend to exhibit lower vaccination rates compared to regions with fewer obstacles [ 180 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these variables specifically apply to the uncertain model, while all models acknowledge the significance of the level of concern. Previous research has reported an association between vaccine uptake in hesitant communities and their level of apprehension regarding the accessibility and distribution of vaccines [ 111 , 112 ]. To this end, regions facing greater hurdles in distributing vaccines, as gauged by the multidimensional CVAC index of concern, tend to exhibit lower vaccination rates compared to regions with fewer obstacles [ 180 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since no information is provided on the number of people or percentage of the population within each level of concern sub-category for social vulnerability, this data could not be transformed into a percentage value. Nonetheless, many studies have used this variable as a seminal measure to understand vaccine hesitancy (e.g., [ 111 , 112 ]); thus, the decision was made to keep it as a variable in this work.…”
Section: Methodsmentioning
confidence: 99%
“…Vaccine hesitancy refers to a situation where people either delay or refuse to get vaccinated, even when vaccines are accessible. (Tolley et al, 2023). There's a limited amount of research on strategies to combat vaccine hesitancy with a focus on influenza, HPV, childhood vaccines, diphtheria, tetanus, pertussis, and polio in the Americas.…”
Section: Vaccine Hesitancy and Strategies Addressing Itmentioning
confidence: 99%